Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2147/dddt.s219350
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparing The Efficacy Of An Anti-Human VEGF-A Neutralizing Antibody Versus Bevacizumab On A Laser-Induced Choroidal Neovascularization (CNV) Rhesus Monkey Model</p>

Abstract: PurposeTo evaluate the efficacy of a therapy on improving characteristics of laser-induced choroidal neovascularization (CNV) via single intravitreal injection of a humanized anti-human VEGF monoclonal antibody (PRO-169) versus bevacizumab in a rhesus monkey model.MethodsTo induce experimental CNV, small high-energy laser spots were used to treat several areas, around the macula in the retinas of monkeys at Day −21. Eighteen rhesus monkeys were used for CNV induction. The efficacy endpoints were fluorescein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(60 reference statements)
0
11
0
Order By: Relevance
“… 5 PRO-169 is a biosimilar candidate to BEV, it is structurally similar and has target specificity like BEV does, but it was developed for intravitreal use. 6 , 7 PRO-169 has been determined to be consistent with historical data such as quality, charge of heterogeneity, purity, structure, and binding affinity of commercially available BEV. 6 …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“… 5 PRO-169 is a biosimilar candidate to BEV, it is structurally similar and has target specificity like BEV does, but it was developed for intravitreal use. 6 , 7 PRO-169 has been determined to be consistent with historical data such as quality, charge of heterogeneity, purity, structure, and binding affinity of commercially available BEV. 6 …”
Section: Introductionmentioning
confidence: 83%
“…In summary, similar inhibitory effects on angiogenesis between PRO-169 and BEV have been demonstrated in an in vivo preclinical study; PRO-169 has proven to have the same effectiveness in reducing the retinal thickness and fluorescein leakage area in a CNV rhesus monkey model. 7 Also, PRO-169 has demonstrated to be nontoxic to the retina at the 1.25 mg dose tested in NZW rabbit eyes. 6 Here, we report the results of the intraocular pharmacokinetics profile after a single intravitreal injection of PRO-169 and, in order to ensure that PRO-169 is safe after repeated injections, three consecutive intravitreal injections were administered at 30-days intervals in a second experiment.…”
Section: Introductionmentioning
confidence: 94%
“…PRO-169, is a mAb structurally like bevacizumab on target specificity, identity and pharmacokinetics, specific for ophthalmic use. On a laser-induced CNV rhesus monkey model, it demonstrated to be able to reduce the retinal thickness and fluorescein leakage area after treatment for 2 and 4 weeks, without toxic effect or adverse events [4]. However, controlled research in an animal model using electrophysiological and clinical tests after repeated intravitreal injections was needed.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these have shown that the repeated intravitreal injections of bevacizumab or ranibizumab have no long-term deleterious effects on the electrophysiological and morphologic integrity of the retina [1,[11][12][13][14][15][16][17]. Another preclinical in vivo study reported that after Choroidal Neovascularization (CNV) induction through retinal photocoagulation, PRO-169 administration (1.25 mg per eye) can inhibit the retinal thickness and fluorescein leakage area without toxic effect or adverse events in a rhesus monkey model [4]. Assessing retinal toxicity of PRO-169, through controlled research in an animal model using ERG and clinical tests after repeated intravitreal (Ivt) injections was needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation